Weed control, yield and quality of small-grain scented rice as influenced by spacing and weed management in lower gangetic plains - Pal, Ashish Kumar; Ghosh, Mrityunjay; Mazumdar, D; Patra, BC; Banerjee, Sibajee (ORYZA-An International Journal of Rice, 2022)
The effect of planting density and weed management on weed control, yield and quality of a non-Basmati type short-grained scented rice (cv. Radhunipagal) was studied at 'C' Block Farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, Nadia, West Bengal. The field experiment was conducted in a split-plot design comprising 2 spacings (15 cm × 15 cm and 20 cm × 15 cm) in main plots and 6 weed control practices [weedy check, 2 hand weeding (HW), Butachlor as pre-emergence (PE) + HW, Butachlor (PE) + 2,4-D Na-salt as post-emergence (PoE), HW + 2,4-D Na-salt (PoE), mechanical weeding + HW) in sub-plots during rainy (kharif) season of 2013 and 2014. Mean number of total weeds in 1 m2 field was 94.3 and 118.8 at 28 and 56 days after transplanting (DAT); and weed control efficiency varied among 5 weed management practices over weedy check as: 49.0-67.3% at 28 DAT and 56.5-72.8% at 56 DAT. Close planting (15 cm × 15 cm) resulted in 9.1% greater grain yield (2.27 vs. 2.08 t/ha), higher net income (Rs. 23,700 vs. 20,900/ha) and B:C ratio (1.79 vs. 1.73) over wider spacing (20 cm × 15 cm). Manual weeding twice at 21 and 42 DAT recorded better weed control efficiency (67.3 and 72.8% at 28 and 56 DAT), grain yield (2.51 t/ha), milling recovery (65.9%) and net return (Rs. 25,900/ha). But chemical weed control [Butachlor (PE) + 2,4-D Na-salt (PoE)] was adjudged as less expensive option (Rs. 27,300/ha) for Radhunipagal rice with moderate grain yield (2.16 t/ha ), higher protein content (7.45%) and B: C ratio (1.90).